Computers that Create Galaxies and See Gravitational Waves. (21st August 2019) - Heck, Lydia
Abstract: Dr Lydia Heck of Durham University's Institute for Computational Cosmology explains the research work at COSMA (aka the Cosmology Machine) and the national Distributed Research using Advanced Computing facility (DiRAC), and what has been achieved so far